WASTEWATER COMPONENTS EFFECT ON METACHROMASIA REACTION OF VOLUTIN GRANULES in vitro - Kharchuk M.S.; Gromozova E.N. (Biotechnologia Acta, 2017)
Microorganisms that contain the polyphosphates volutin granules take active part in phosphorus and heavy metals removal from the wastewater. The metachromatic reaction is a simple cytochemical method for the detection of these granules. The objective of current research was to study the metachromatic reaction of inorganic polyphosphate with Methylene Blue dye in combination with other components of wastewater (proteins, carbohydrates, metal ions) in vitro. It was demonstrated that manifestation of metachromatic coloration depends on the polyphosphate concentration and to a lesser extent, on its chain length. Glucose did not influence metachromasy reaction. At the same time, calcium ions and bovine serum albumin, depending on their concentration, stimulated or inhibited the metachromatic color of the test solutions. Bovine serum albumin, in contrast to calcium ions, had a lesser effect on metachromasy. Thus, the abundant accumulation of polyphosphates and metal cations (as we demonstrated with of Ca2+ ions), in microorganisms of activated sludge not always accompanied by a pronounced reaction of metachromasy of the volutin granules. In this regard, the use of other cytochemical methods for the identification of polyphosphate granules is recommended, for example, staining with fluorescent dye 4’,6-diamidino-2-phenylindole (DAPI).